Alinhamento entre cultura organizacional e valores relativos ao trabalho em uma instituição financeira - Silva, Rodrigo Augusto Quintiliano da (Universidade Federal de São Carlos, 2015)
Organizational Culture is a theme that has been gaining interest in the academic area and in business management, mostly since the 1980's. Organizational culture can be understood as a set of assumptions, values, and artifacts transmitted between its members, creating a meaning which defines a behavior pattern in an organization. This study aimed to analyze the alignment between cultural and work related values of potential employees in a Brazilian Financial Institution. It was relevant for the studied company to analyze the expectations of the new employees, since these expectations may or may not converge with the present cultural values, influencing these people. Since the organizational culture rules the company and its member's behaviors, according to the definition, it is believed that the analysis of the alignment between work related values and the organizational culture is an important diagnostic tool for strategic actions. The research was developed in a large financial institution, of mixed economy, and because of this fact, it shows the coexistence between public and private values. By performing a survey between the potential employees of that organization (approved in a public examination and summoned to take office), it was possible to identify the values that would orientate their work life and, afterwards, these values were compared to the cultural values already existing in the company. With regard to corporate values (declared by the organization), an alignment in the ones related to safety, accomplishment, universalism, and benevolence was observed. As far as organizational values go (values shared by the organization members), there was an alignment in those related to safety, conformity, and self-determination, as well as a partial alignment in the values related to realization, universalism, and benevolence. Considering both types of values as representatives of the company's organizational culture, we found an alignment in safety values and a misalignment in the values related to power, dominance, and prestige. The lack of alignment in these values must be observed by the company, since that can influence the satisfaction of new employees with their work negatively, contribute to a higher turnover rate, and even influence the financial performance of the company. Additionally, the new employees values can, over time, modify the company's culture itself.
Keywords: Cultura organizacional; Instituições financeiras; Survey; Valores; Financial institution; Organizational culture; Organizational values; Work related values; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO